Análise histológica, morfométrica, expressão de genes, proteínas e western blot na retina de ratos com glaucoma induzido e tratados com citrato de sildenafil - Zanoni, Diogo Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
O glaucoma é a principal causa global de cegueira irreversível e o número de pessoas com glaucoma em todo o mundo aumentará para 111,8 milhões em 2040, mesmo com os tratamentos vigentes. Deste modo, enseja uma necessidade de desenvolver terapias neuroprotetoras que possam ser usadas para reduzir os efeitos perniciosos do glaucoma, como a morte de células ganglionares da retina (CGR). Avanços na compreensão da fisiopatologia do glaucoma é um fator chave na compreensão da patogênese da neuropatia glaucomatosa. Neste contexto a isquemia retiniana desempenha um papel central em várias doenças da retina. A patogênese da isquemia retiniana envolve alterações temporais da morfologia e morfometria da retina assim como mudanças na expressão gênica e protéica. O Citrato de Sildenafila (SC) mostrou efeito protetor nos modelos de isquemia/reperfusão (I/R) com efeitos neuroprotetores. Contudo, a administração oral de CS, em humanos, encontra inúmeros efeitos colaterais, tais como redução da pressão arterial, dores de cabeça, rubor e congestão nasal são concomitantes,

Glaucoma is the leading global cause of irreversible blindness and the number of people with glaucoma worldwide will increase to 111.8 million by 2040, even with current treatments. Thus, there is a need to develop neuroprotective therapies that can be used to reduce the deleterious effects of glaucoma, such as retinal ganglion cell death (RBC). Advances in understanding the pathophysiology of glaucoma are a key factor in understanding the pathogenesis of glaucomatous neuropathy. In this context, retinal ischemia plays a central role in various diseases of the retina. The pathogenesis of retinal ischemia involves temporal changes in retinal morphology and morphometry as well as changes in gene and protein expression. Sildenafil Citrate (SC) showed protective effect in the ischemia / reperfusion (I / R) models with neuroprotective effects. However, oral administration of CS in humans finds numerous side effects such as reduced blood pressure, headaches, flushing and nasal congestion are concomitant, as well as patients with moderate to severe cardiovascular disease or those undergoing nitrate therapy have increased secondary risks for adverse cardiovascular effects. Thus, we propose that the eye drops administration of CS may be an alternative to the oral route and also be equally neuroprotective in glaucoma and may minimize the undesirable risks in the systemic use of this drug, as well as offer a new approach for the therapeutic intervention in the pathogenesis of neuropathy glaucomatous. If our results are positive, in such a comprehensive study, it may lead to a clinical trial of this safe and promising drug in patients with glaucoma.
Histological, morphometric analysis, expression of genes, proteins and western blot in the retina of glaucoma-induced rats and treated with sildenafil citrate
Keywords: Apoptose; Glaucoma; Células ganglionares da retina; Citrado de Sildenafil tópico; Apoptosis; Retinal ganglion cells; Eye drops; Citrate Sildenafil